Association of tumor location with economic outcomes and air leak complications in thoracic lobectomies: results from a national hospital billing dataset - Bhora F; Ghosh SK; Kassis E; Yoo A; Ramisetti S; Johnston SS; Rehmani S; Kalsekar I (ClinicoEconomics and Outcomes Research, 2019)
Faiz Bhora,1 Sudip K Ghosh,2 Edmund Kassis,3 Andrew Yoo,4 Sushama Ramisetti,4 Stephen S Johnston,4 Sadiq Rehmani,5 Iftekhar Kalsekar41Health Quest Health System, Poughkeepsie, NY 12601, USA; 2Global Health Economics and Market Access, Ethicon, Inc., Cincinnati, OH, USA; 3Medical Affairs, Ethicon, Inc., Cincinnati, OH, USA; 4Medical Devices - Epidemiology, Johnson and Johnson, New Brunswick, NJ, USA; 5Department of Thoracic Surgery, Mount Sinai St. Luke‘s Hospital, Icahn School of Medicine at Mount Sinai, New York, NY, USAPurpose: To assess whether tumor location during thoracic lobectomies affects economic outcomes or air leak complications.Patients and methods: Retrospective, observational study using Premier Healthcare Database. The study included patients aged ≥18 years who underwent elective inpatient thoracic lobectomy for lung cancer between 2012 and 2014 (first qualifying=index admission). Three mutually exclusive tumor location groups were formed: upper lobe, middle lobe, and lower lobe. Primary outcomes were index admission’s length of stay (LOS), total hospital costs, and operating room time; in-hospital air leak complications (composite of air leak/pneumothorax) served as an exploratory outcome. Multivariable models were used to examine the association between tumor location and the study outcomes, accounting for covariates and hospital-level clustering.Results: 8,750 thoracic lobectomies were identified: upper lobe (n=5,284), middle lobe (n=512), and lower lobe (n=2,954). Compared with the upper lobe, the middle and lower lobe groups had statistically significant (p<0.05): shorter adjusted LOS (7.0 days upper vs 5.8 days middle, 6.6 days lower), lower adjusted mean total hospital costs ($26,177 upper vs $23,109 middle, $24,557 lower), and lower adjusted odds of air leak complications (odds ratio middle vs upper=0.81, 95% CI=0.74–0.89; odds ratio lower vs upper=0.60, 95% CI=0.46–0.78). Findings were similar but varied in statistical significance when stratified by open and video-assisted thoracoscopic surgery approach.Conclusion: Among patients undergoing elective thoracic lobectomy for lung cancer in real-world clinical practice, upper lobe tumors were significantly associated with increased in-hospital resource use and air leak complications as compared with lower or middle lobe tumors.Keywords: thoracic lobectomy, costs, length of stay, cancer